PAK2-driven cytoskeleton–endosome dynamics control macrophage hyperphagia and SIRPA engagement - Julie Drieu La Rochelle; Joseph P. Cassidy; Jonathan Chernoff; Ulla G. Knaus (Proceedings of the National Academy of Sciences, 2025)
Macrophages rely on dynamic cytoskeletal rearrangements to respond to their environment. This plasticity supports biomechanical transitions and functional polarization, mediating tissue homeostasis, antimicrobial defense, and repair processes. In the tumor environment context-specific reprogramming leads to functional diversification, from antitumorigenic to immunosuppressive phenotypes. Altering cytoskeletal dynamics modifies macrophage behavior and holds promise to shift their profile toward desired features. Here, we show that abolishing the activity of the serine/threonine kinase PAK2 transforms macrophage properties, resulting in abundant membrane expansion and amplified engulfment of diverse targets. Simultaneously, PAK2 is essential to coordinate endosomal receptor trafficking including SIRPA recycling to the cell surface. In vivo PAK1 and PAK2 cooperate in restraining oxidative responses, and in maintaining cytokinetic fidelity and gut barrier integrity to safeguard from a macrophage-driven hematologic malignancy associated with low-grade inflammation. Targeted interference with PAK2 holds promise in immunotherapy by harnessing hyperphagia and SIRPA sequestration for accelerated cancer cell killing.